Encapsulation of Metalloporphyrins in a Self‐Assembled Cubic M8L6 Cage: A New Molecular Flask for Cobalt–Porphyrin‐Catalysed Radical‐Type Reactions. Issue 31 (2nd July 2013) - Otte, Matthias; Kuijpers, Petrus F.; Troeppner, Oliver; Ivanović‐Burmazović, Ivana; Reek, Joost N. H.; de Bruin, Bas
Abstract The synthesis of a new, cubic M8L6 cage is described. This new assembly was characterised by using NMR spectroscopy, DOSY, TGA, MS, and molecular modelling techniques. Interestingly, the enlarged cavity size of this new supramolecular assembly allows the selective encapsulation of tetra(4‐pyridyl)metalloporphyrins (MII(TPyP), M=Zn, Co). The obtained encapsulated cobalt–porphyrin embedded in the cubic zinc–porphyrin assembly is the first example of a catalytically active encapsulated transition‐metal complex in a cubic M8L6 cage. The substrate accessibility of this system was demonstrated through radical‐trapping experiments, and its catalytic activity was demonstrated in two different radical‐type transformations. The reactivity of the encapsulated CoII(TPyP) complex is significantly increased compared to free CoII(TPyP) and other cobalt–porphyrin complexes. The reactions catalysed by this system are the first examples of cobalt–porphyrin‐catalysed radical‐type transformations involving diazo compounds which occur inside a supramolecular cage.